Effect of Feeding on Growth Patterns of Vaname Shrimp (Litopeanus Vannamei) in Biofloc Ponds in Dowora Village, Tidore Islands City - Dani Kamaruddin; Ahmad Talib; Ibnu W. Laitupa; Syahnul S. Titaheluw (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Vaname shrimp (Litopeanus vannamei), known as white shrimp, is an introduced species from the waters of Central America and countries in Central and South America such as Ecuador, Venezuela, Panama, Brazil and Mexico that has not been cultured in Indonesia for a long time. In recent years, the main contributing commodity to the aquaculture sector in Indonesia is white shrimp. Vaname shrimp was officially released in 2001 and since then the role of vaname is very real to replace the tiger shrimp (Penaeus monodon) agro-industry which is the original Indonesian shrimp that has decreased and failed production due to technical and non-technical factors. This research was conducted in the vaname shrimp farming pond of Muhammadiyah University of North Maluku, located in Dowora Village, Tidore Islands City in April-June 2023. The amount of feed given must be in accordance with the needs of shrimp in the pond, so as not to experience a lack of feed or excess feed. Shrimp need a lot of protein in its growth, generally the protein needed by shrimp in a higher percentage compared to other animals. Protein is the nutrient that plays the most role in shrimp growth. Shrimp need for protein is different for each life stadia.